If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 = 7 + 4x Solving -5 = 7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -5 + -4x = 7 + 4x + -4x Combine like terms: 4x + -4x = 0 -5 + -4x = 7 + 0 -5 + -4x = 7 Add '5' to each side of the equation. -5 + 5 + -4x = 7 + 5 Combine like terms: -5 + 5 = 0 0 + -4x = 7 + 5 -4x = 7 + 5 Combine like terms: 7 + 5 = 12 -4x = 12 Divide each side by '-4'. x = -3 Simplifying x = -3
| 2c+3=4(5c-6) | | 4(2x+3)+5=1 | | -5x-4(-7-4x)=36+7x | | 60=4(5-x) | | 2(5+x)=-30 | | x-21=-x*2 | | 3(7x-7)=-6+6x | | 4x-148=3x+566 | | 50+0.9*(y-30)+10+10+28=y | | 5[2-3(x-8)]=26-8x | | (2x^4)+16x=0 | | 2x+(-4x)=22 | | 4x+9-49=0 | | -1+3(v-7)=-28 | | 2x^2+22x+60=x | | 20y+13=15y-8 | | 4x+4x=64 | | (18a^3)-72a=0 | | z-0.45=5.97 | | 3a+(4b+2)I=9-6I | | 50+0.9*(y-30)=y | | -5x+24=-8(x-6)+6x | | -(-a)= | | 3x(4)=2 | | -n+n= | | 2(4z-2)-2(5-3z)=4 | | 5x+5=4x+4 | | 11+2(3n-11)=1 | | 6((2n^2)+3n-35)=0 | | (3x+4)-30=0 | | t-45=-48 | | 4x+8y-3x+2y= |